The “Top-Down” Approach to the Evaluation of Children with Febrile Urinary Tract Infection - Hans G. Pohl; A. Barry Belman (Advances in Urology)
The evaluation of children presenting with urinary tract infection (UTI) has long entailed sonography and cystography to identify all urological abnormalities that might contribute to morbidity. The identification of vesicoureteral reflux (VUR) has been of primary concern since retrospective studies from the 1930s to 1960s established a strong association between VUR, recurrent UTI, and renal cortical scarring. It has been proposed that all VUR carries a risk for renal scarring and, therefore, all VUR should be identified and treated. We will not discuss the controversies surrounding VUR treatment in this review focusing instead on a new paradigm for the evaluation of the child with UTI that is predicated on identifying those at risk for scarring who are most deserving of further evaluation by cystography.